Dalit personal narratives : reading caste, nation, and identity - Kumar, Raj, 1967- (New Delhi : Orient BlackSwan, 2010)
In Indian context.
Includes bibliographical references (p. [262]-288) and index.
Keywords: Indic prose literature -- 20th century -- History and criticism; Indic prose literature -- Dalit authors -- Biography; Autobiography -- Dalit authors -- History and criticism; Dalits -- India -- Biography -- History and criticism